Changes of Intra Ocular Pressure After Nd: Yag Laser Capsulotomy in Rangpur Medical College Hospital (Journal of Rangpur Medical College, 2024)
Background: Posterior capsule opacification is the most common disabling sequelae of modern cataract surgery. In Bangladesh we are practicing Nd: YAG laser capsulotomy in treating posterior capsule opacification. Objective: This study was carried out to evaluate intraocular pressure before and after performing Nd: YAG laser capsulotomy in posterior capsular opacification. Methods: A prospective study conducted at Ophthalmology Department, Rangpur Medical College Hospital from July to December 2018 focused on diagnosing and treating posterior capsular opacification with Nd: YAG laser of 50 patients. Patients underwent thorough ophthalmic evaluations before receiving laser treatment by a consultant ophthalmologist. Key information including patient details, pre-laser IOP measurements, laser parameters, and post-procedure IOP measurements were recorded after 60 minutes, 24 hours, 7 days, 14 days, 30 days in a specially designed proforma. Results: The baseline average IOP was 13.24. After one hour of ND: YAG Laser capsulotomy, 41 patients (82%) had raised IOP. There were no changes in IOP in 9 patients (18%). Six of the nine patients were in the 40-60 mj energy group, while three were in the 61-80 mj energy group. All patients who received high energy (81-100 mJ) had a statistically significant rise in IOP. IOP returned to baseline levels within 7 days of ND:YAG Laser capsulotomy with no intervention, and remained normal after 14 and 30 days. Conclusion: The result suggested that a transient rise of intraocular pressure occurs almost invariably. High energy level used during Nd:YAG Laser capsulotomy had significantly more chances of raised IOP. But IOP comes to almost baseline within 7 days without any interventions. It is recommended that each patient undergoing Nd:YAG laser capsulotomy should receive minimum amount of energy and patient should be followed up for rise in IOP and managed accordingly.J Rang Med Col. September 2024; Vol. 9, No. 2: 56-60